Evolution of lipid damage and volatile amine content in Patagonian squid (Doryteuthis gahi) by‐products during frozen storage. (6th June 2022) - Aubourg, Santiago P.; Trigo, Marcos; González, Mª Jesús; Lois, Salomé; Medina, Isabel
Summary: By‐products (viscera, tails, skin, etc .) resulting from Patagonian squid ( Doryteuthis gahi ) commercialisation were pooled together and stored at −10 and –18 °C for 12 months. During this storage time, 81.1–83.7 and 1.7–2.4 (g 100 g −1 ) ranges were detected for moisture and lipid values, respectively. An increased storage time and temperature led to free fatty acid formation and phospholipid content decrease ( P  < 0.05). Meantime, peroxide levels were low and included in 2.1–3.6 meq. active oxygen kg −1 lipids range. Contrary, substantial formation ( P  < 0.05) of thiobarbituric acid reactive substances and fluorescent compounds was proved, values being higher by increasing the time and temperature of storage of squid by‐products. Related to amine formation, trimethylamine values increased notably ( P  < 0.05) with storage, higher values being obtained by increasing the storage time and temperature. For total volatile amines, increased levels with storage time were detected in samples stored at −10 °C; contrary, by‐products stored at the lowest temperature tested did not provide differences ( P >  0.05), resulting from the storage time. This study shows the need of appropriate storage conditions to offer the current by‐products as a source of valuable marine constituents. Present results meet the present global interests in the search for new and undervalued marine substrates to be employed commercially. Abstract : Assessment of quality loss in frozen squid by‐products.